An Experimental Investigation Of Piezoelectric P (VDF-TrFE) Thick Film On Flexible Substrate As Energy Harvester - Chow, Khoon Keat; Kok, Swee Leong; Lau, Kok Tee (Institute Of Physics (IOP) Publishing, 2017)
This paper proposes an experimental investigation of energy harvester using poly(vinylidene fluoride-trifluoroethylene) or P(VDF-TrFE) thick-film on flexible substrate by using print screen and rod method. Polyester film being used as the substrate where a sandwiched layer of electrode-piezopolymer-electrode thick film is deposited on. The thick-film is then annealed at 100°C and polarized at 100 V for the film with a thickness of about 18µm, being inspected under EDX, FESEM and XRD. The fabricated energy harvester piezoelectric is able to generate a maximum output power of 4.36 µW at an externa l electrical load of 1 kΩ with a maximum peak-to-peak of about 3.0V when an impact free-fall force of 0.2N was applied on the thick-film.